Hybrid wireless optics (HWO): Building the next-generation home network - Bouchet, O; El Tabach, M; Wolf, M; O'Brien, D; Faulkner, G; Walewski, J; Randel, S; Franke, M; Nerreter, S; Langer, K; Grubor, J; Kamalakis, T (2008)
Gigabit home access networks (HANs) are a pivotal technology to be developed if the European Union (EU) Vision of the Future Internet is to be realised. Consumers will require such HANs to be simple to install, without any new wires, and easy enough to use so that information services running on the HAN will be "just another utility," as, for instance, electricity, water and gas are today. The hOME Gigabit Access (OMEGA) HAN project [1] aims at bridging the gap between home and access network, providing Gbit/s connectivity to users. The project considers a combination of various technologies such as radio frequency (RF) and free-space or wireless optical links (FSO - operating at infrared and visible wavelengths) in order to meet user demands and provide wireless connectivity within and the home and its surroundings. When combined with power-line communications this enables a home backbone that meets the "without new wires" vision. A technology-independent MAC layer will control this network and provide services as well as connectivity to any number of devices the user wishes to connect to it in any room in a house/apartment, and further, this MAC layer will allow the service to follow the user from device to device. In order to make this vision come true, substantial progress is required in the fields of optical-wireless physical layers, in protocol design, and in system architecture. © 2008 IEEE.